Tumor-derived colorectal cancer organoids induce a unique Treg cell population by directing CD4+ T cell differentiation - Sonia Aristin Revilla; Cynthia L. Frederiks; Stefan Prekovic; Enric Mocholi; Onno Kranenburg; Paul J. Coffer (iScience)
Summary: In colorectal cancer (CRC), increased numbers of tumor-infiltrating CD4+ regulatory T (Treg) cells correlate with tumor development, immunotherapy failure, and poor prognosis. To assess how CRC tumors directly modulate Treg cell differentiation, we developed an in vitro co-culture system using CD4+ T cells from Foxp3eGFP mice and CRC tumor-derived organoids. Co-culture resulted in a significant increase in Treg cell numbers. RNA-sequencing identified a distinct transcriptional profile of CRC organoid-induced Treg cells, with upregulation of genes associated with CRC Treg cells in vivo. High expression of genes upregulated in CRC organoid-induced Treg cells correlates with shorter progression-free intervals and overall survival in CRC patients. Human CRC organoids similarly induced Treg cells with enhanced suppressive capacity and upregulated genes linked to CRC Treg cells in vivo. This model provides insights into how CRC tumors modulate CD4+ T cell differentiation and can identify approaches to disrupt Treg cells and stimulate anti-tumor immunity.